2016
DOI: 10.1002/chin.201626211
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Lanostane‐Type Triterpenes from the Fungal Endophyte Scleroderma UFSMSc1 (Persoon) Fries.

Abstract: Lanostane-Type Triterpenes from the Fungal Endophyte Scleroderma UFSMSc1 (Persoon) Fries. -Two lanostane triterpenoids, sclerodol A (Ia) and B (Ib), are isolated from the culture of Eucalyptus grandis derived from the endophyte Scleroderma UFSMSc1 (Persoon) Fries. They show promising anticandidal activities. -(MORANDINI, L. M.; NETO, A. T.; PEDROSO, M.; ANTONIOLLI, Z. I.; BURROW, R. A.; BORTOLUZZI, A. J.; MOSTARDEIRO, M. A.; DA SILVA, U. F.; DALCOL, I. I.; MOREL*, A. F.; Bioorg. Med. Chem. Lett. 26 (2016) 4, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…These results confirmed the anti‐dengue potential of triterpenoids endowed with a lupane‐type skeleton, as exemplified by betulinic acid 3 β ‐caffeate, which significantly inhibited RdRp activity . More generally, antiviral properties of betulinic acid ( 4 ), betulin ( 5 ) and betulinic aldehyde ( 6 ), the three most common molecules of this chemical series, have been often reported against various types of viruses …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…These results confirmed the anti‐dengue potential of triterpenoids endowed with a lupane‐type skeleton, as exemplified by betulinic acid 3 β ‐caffeate, which significantly inhibited RdRp activity . More generally, antiviral properties of betulinic acid ( 4 ), betulin ( 5 ) and betulinic aldehyde ( 6 ), the three most common molecules of this chemical series, have been often reported against various types of viruses …”
Section: Resultssupporting
confidence: 76%
“…Previous studies have shown that endophytes were able to produce triterpenoids. For example, lanostane‐type triterpenoids were isolated from the endophytes Scleroderma sp., Ceriporia lacerate , and Diaporthe sp . Oleane‐type triterpenoids were isolated from Xylaria papulis , Pestalotiopsis clavispora , and ursane‐type triterpenoids were isolated from Annulohypoxylon stygium and Pestalotiopsis clavispora .…”
Section: Resultsmentioning
confidence: 99%
“…A group of triterpene and steroids were also found including epidihydrocholesterin, androstenediol, and methandriol. Several reports of related structures for these compounds also support our findings as hit candidates [60][61][62][63][64][65]. Two tropane derivatives were also found, they are structurally related to benzotropine which has been reported as active [57].…”
Section: Ligand-based Virtual Screeningsupporting
confidence: 88%